Extracellular Adenosine Triphosphate and Chronic Obstructive Pulmonary Disease - Lommatzsch, Marek; Cicko, Sanja; Müller, Tobias; Lucattelli, Monica; Bratke, Kai; Stoll, Paul; Grimm, Melanie; Dürk, Thorsten; Zissel, Gernot; Ferrari, Davide; Di Virgilio, Francesco; Sorichter, Stephan; et al. (American journal of respiratory and critical care medicine, 2010)
Extracellular ATP promotes inflammation, but its role in chronic obstructive pulmonary disease (COPD) is unknown. To analyze the expression of ATP and its functional consequences in never-smokers, asymptomatic smokers, and patients with COPD. ATP was quantified in bronchoalveolar lavage fluid (BALF) of never-smokers, asymptomatic smokers, and patients with COPD of different severity. The expression of specific ATP (purinergic) receptors was measured in airway macrophages and blood neutrophils from control subjects and patients with COPD. The release of mediators by macrophages and neutrophils and neutrophil chemotaxis was assessed after ATP stimulation. Chronic smokers had elevated ATP concentrations in BALF compared with never-smokers. Acute smoke exposure led to a further increase in endobronchial ATP concentrations. Highest ATP concentrations in BALF were present in smokers and ex-smokers with COPD. In patients with COPD, BALF ATP concentrations correlated negatively with lung function and positively with BALF neutrophil counts. ATP induced a stronger chemotaxis and a stronger elastase release in blood neutrophils from patients with COPD, as compared with control subjects. In addition, airway macrophages from patients with COPD responded with an increased secretion of proinflammatory and tissue-degrading mediators after ATP stimulation. These findings were accompanied by an up-regulation of specific purinergic receptors in blood neutrophils and airway macrophages of patients with COPD. COPD is characterized by a strong and persistent up-regulation of extracellular ATP in the airways. Extracellular ATP appears to contribute to the pathogenesis of COPD by promoting inflammation and tissue degradation.